Erhvervsfrekvens i Grønland: Analyse af situationen i 2000 - Lars Lund (Copenhagen Business School (CBS), Department of Economics, 2006)
– Participation rate on the Greenland labour market: situation of year 2000. A goal is that a large part of the population of normal working age is employed. The participation rate is one of the statistics used to describe the performance of the economy in this respect. Two sources are used to arrive at an estimate of the rate both for Greenland in general and for four regions defined by four so called growth towns: Nuuk, Sisimiut, Ilulissat and Qaqortoq. They are Statistic Greenland's publications on employment and on unemployment. There are some difficulties using the available data: the employment and unemployment surveys refer to periods whereas the potential workforce is counted at a date. Furthermore persons with yearly income below an arbitrary limit of 40.000 DKK are sorted out even though they should contribute to the number of full year employed. The participation rate is found to be much higher in Nuuk than in the other regions. For Greenland as such the number is in line with figures for Western Europe and North America. Characteristics of people not in the work force are looked for. To some extent a connection exists to the number people receiving pension as disabled, people in education, and those on leave because of childbirth, but the relation is imperfect and great differences are seen between regions.
hdl:10398/7604
Keywords: H00; 330; Greenland; labour market; employment; unemployment